2005
DOI: 10.1002/art.21236
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor prevents alendronate-induced osteoclast apoptosis in vivo by stimulating Bcl-xL expression through Ets-2

Abstract: Objective. To investigate why bisphosphonates are less effective at preventing focal bone loss in rheumatoid arthritis (RA) patients than in those with generalized osteoporosis, and the mechanisms involved.Methods. The response of osteoclasts to alendronate (ALN) in tumor necrosis factor-transgenic (TNFTg) mice that develop erosive arthritis and in wild-type littermates was studied. TNF-Tg and wild-type mice were given ALN, and the osteoclast numbers in the inflamed joints and in the long bones were compared. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 46 publications
3
45
1
3
Order By: Relevance
“…Because M-CSF is constitutively expressed in the bone microenvironment in vivo, and TNF␣ stimulates osteoblasts and T lymphocytes to up-regulate their expression of M-CSF (16,17), TNF␣-induced c-Fms expression must work through both M-CSF-dependent and -independent mechanisms. We have reported previously that TNF␣ promotes mature osteoclast survival (33). However, we did not observe clear changes in OCP apoptosis.…”
Section: Discussioncontrasting
confidence: 81%
“…Because M-CSF is constitutively expressed in the bone microenvironment in vivo, and TNF␣ stimulates osteoblasts and T lymphocytes to up-regulate their expression of M-CSF (16,17), TNF␣-induced c-Fms expression must work through both M-CSF-dependent and -independent mechanisms. We have reported previously that TNF␣ promotes mature osteoclast survival (33). However, we did not observe clear changes in OCP apoptosis.…”
Section: Discussioncontrasting
confidence: 81%
“…After confirmation of the VEGF-C sequence by DNA sequencing, VEGF-C was cloned into the EcoRI site of the pMX-IRES-GFP vector provided by Dr. Matsuo Koichi. The retrovirus vector was transfected into the Plat-E retroviral packaging cell line, and viral supernatant was collected 48 h later for infection as we described previously (31,33). pMX-GFP plasmid was used as control vector.…”
Section: Animals-wtmentioning
confidence: 99%
“…The cells were then cultured with 1:20 diluted conditioned medium containing M-CSF (from an M-CSF-producing cell line) (34) and RANKL with or without additional treatment to form mature osteoclasts. Alternatively, the cells were cultured with M-CSF for 3 days to generate OCPs, as we described previously (33), and then infected with retroviral supernatants and cultured with M-CSF and RANKL on bone slices to form mature osteoclasts. The cells were fixed and stained for tartrate-resistant acid (TRAP) activity to identify osteoclasts as TRAP ϩ cells containing at least three nuclei and then removed and stained with 0.5% toluidine blue to visualize resorption pits for bone resorption activity, as we described previously (31,33).…”
Section: Animals-wtmentioning
confidence: 99%
“…Pioneering work by Roodman and coworkers demonstrated that the targeting of Bcl-xL and SV40 large T antigen to cells of the osteoclast lineage in transgenic mice under the control of the TRAP promoter immortalized osteoclast precursors (19). Zhang et al reported that TNF-α inhibited alendronate-induced apoptosis of osteoclasts by stimulating Bcl-xL expression (20). On the other hand, Jimi et al (21) reported that Bcl-2 and Bcl-xL in osteoclasts were not upregulated by RANKL treatment.…”
Section: Discussionmentioning
confidence: 99%